Injection of Supercritical Carbon Dioxide into Granitic Rock and its Acoustic Emission Monitoring. (2017) - Ishida, Tsuyoshi; Desaki, Shuich; Yamashita, Hiroto; Inui, Shuhei; Naoi, Makoto; Fujii, Hirokazu; Katayama, Tatsuo
Abstract: We injected carbon dioxide (CO2 ) into a hole drilled around 8 m long in a granitic hot rock from the floor of the tunnel. We drilled four AE (acoustic emission) monitoring holes parallel 1 m far away from the injection hole and monitored AE events induced with hydraulic fracturing (HF). When the breakdown (BD) pressure was recorded, the pressure and the temperature satisfied the supercritical condition of CO2 . The AE source distribution showed that two vertical cracks were initiated from the injection hole with BD. After 75 seconds from the occurrence of BD with no pressure increase, the AE sources started to distribute along the direction almost normal to that of the initial crack from the position around 0.7 m far away from the injection hole. It is most likely that the cracks initiated in intact rock with BD by HF and one of them bended and extended along pre-existing crack. These results suggest that CO2 migrates easily and enhances AE occurrence in a pre-existing joint.